Pertanggung Jawaban Pidana Korporasi Sebagai Pelaku Tindak Pidana Korupsi: Studi Kasus Pada Peningkatan Jalan Nanti Agung - Dusun Baru Kabupaten Seluma (International Forum of Researchers and Lecturers, 2023)
Corruption crimes that occur in Indonesia are increasingly developing in various sectors and are not only carried out by individuals but by corporations. However, the fact is that law enforcement still rarely touches cases of crimes committed by corporations, let alone holding these corporations accountable. The problems raised in this paper are: 1) What is the criminal responsibility of corporations as perpetrators of criminal acts of corruption in the case of the Nanti Agung road improvement project, Seluma Regency. 2) What were the judge's legal considerations in sentencing 8 suspects, including the former Head of the Seluma DPU Department? The approach method used in this research is literature study. Based on the research, the following results were obtained: 1) Corporate criminal liability as perpetrators of criminal acts of corruption in the case of the Nanti Agung road improvement project, Seluma Regency is the imposition of criminal liability on 8 suspects including the former Head of the Seluma DPU Department. 2) The basis of the judge's legal considerations in sentencing to 8 suspects, including the former Head of the Seluma DPU, was that the elements of the Corruption Crime were fulfilled, juridical considerations, as well as aggravating and mitigating factors. The author believes that the appropriate model of criminal liability is the imposition of criminal liability on corporations and corporate managers, so that there is a deterrent effect for corporations.